2010
DOI: 10.1007/s00520-010-0853-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral health care reduces the risk of postoperative surgical site infection in inpatients with oral squamous cell carcinoma

Abstract: Oral health care may reduce the risk of postoperative WI in patients with OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
4
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 15 publications
3
51
4
4
Order By: Relevance
“…Previous studies have identified a significant association between blood loss and frequency of surgical site infection in patients who underwent head and neck surgery (6,11,12). In the present study, no significant differences in regards to the occurrence of postoperative infectious complications between patients with low blood loss (11.1%) and those with high blood loss (15.0%) were observed, although postoperative complications showed a declining tendency in the former group.…”
Section: A B Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Previous studies have identified a significant association between blood loss and frequency of surgical site infection in patients who underwent head and neck surgery (6,11,12). In the present study, no significant differences in regards to the occurrence of postoperative infectious complications between patients with low blood loss (11.1%) and those with high blood loss (15.0%) were observed, although postoperative complications showed a declining tendency in the former group.…”
Section: A B Discussioncontrasting
confidence: 58%
“…Therefore, proper oral health care during the perioperative period is thought to be necessary to decrease the number of oral pathogens. A previous study showed that oral care is essential to decrease surgical site infection in oral cancer patients (6). In addition, preoperative oral care was shown to reduce inflammation during the early postoperative stage in oral cancer patients who underwent a combination of surgical resection with neck dissection and free-flap transplantation, or pectoralis major myocutaneous flap transplantation (7).…”
Section: A B Discussionmentioning
confidence: 99%
“…To achieve oral health, reduction and prevention of these diseases is required; therefore, oral care aiming at improvement and maintenance of oral hygiene to prevent these two major dental diseases should be promoted. Recently, proper oral hygiene is also thought to be essential for maintaining and improving systemic health, especially prevention of (1) aspiration pneumonia in the frail and elderly, and (2) post-operative infections [35]. Various combinations of measures and purposes of oral health maintenance (oral care) are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly radical neck dissection are accompanied with a higher risk for postoperative wound infections to be addressed in the postoperative care [134]. Surgeries in the oral cavity have a higher risk of infection in case of initially reduced oral hygiene and thorough previous care can reduce this risk [137]. As mentioned earlier general risk factors for a higher rate of wound infections are a high tumor stage, smoking, alcohol, diabetes, previous radiation therapy, anemia and low albumin, flap surgeries, mandibulotomy, tracheostomy, blood transfusions and again a prolonged surgery time.…”
Section: Wound Management Antibioticsmentioning
confidence: 99%